2004
DOI: 10.1890/01-6006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Limitation of Biomass Growth in a Tropical Secondary Forest

Abstract: Abstract. Understanding secondary successional processes in Amazonian terrestrial ecosystems is becoming increasingly important as continued deforestation expands the area that has become secondary forest, or at least has been through a recent phase of secondary forest growth. Most Amazonian soils are highly weathered and relatively nutrient poor, but the role of nutrients as a factor determining successional processes is unclear. Soils testing and chronosequence studies have yielded equivocal results regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
200
5
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(233 citation statements)
references
References 34 publications
17
200
5
11
Order By: Relevance
“…In contrast, a review by LeBauer and Treseder (2008) suggested that tropical forests may exhibit N limitation to NPP. Outside of forests on young Hawaiian soils, the results in LeBauer and Treseder (2008) are strongly influenced by responses in dry tropical forests (Campo and Vazquez-Yanes 2004), early successional humid forests (Davidson et al 2004), and high elevation ([2000 masl) tropical forests (Tanner et al 1992). For a mature Indonesian lowland tropical forest on highly weathered soils included in the review, NPP did not respond to N fertilization (Mirmanto et al 1999), and a Hawaiian study on old, highly weathered soils also did not observe a response of NPP to N fertilization (Harrington et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a review by LeBauer and Treseder (2008) suggested that tropical forests may exhibit N limitation to NPP. Outside of forests on young Hawaiian soils, the results in LeBauer and Treseder (2008) are strongly influenced by responses in dry tropical forests (Campo and Vazquez-Yanes 2004), early successional humid forests (Davidson et al 2004), and high elevation ([2000 masl) tropical forests (Tanner et al 1992). For a mature Indonesian lowland tropical forest on highly weathered soils included in the review, NPP did not respond to N fertilization (Mirmanto et al 1999), and a Hawaiian study on old, highly weathered soils also did not observe a response of NPP to N fertilization (Harrington et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Second, carbon allocation should fall in the intervals given by the ground measurements. Then, because photosynthesis increases with nutrient availability (Davidson et al, 2004;Quesada et al, 2009), and because allocation does not seem to vary with it , model photosynthesis parameters could be adjusted to reach the NPP AGW value derived from AGWB and Eq. (7).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…N and P often co-limit plant growth in some ecosystems, and P limitation has been observed in equatorial regions, tropical forests, and freshwater ecosystems (Davidson et al 2004). Supplying both N and P can enhance the growth and reproduction of photosynthetic biota as well as large-scale ecosystem primary production (Elser et al 2007;LeBauer and Treseder 2008).…”
Section: à2mentioning
confidence: 99%